Rhodium-Catalyzed Asymmetric Addition of Arylboronic Acids to Glyoxylates: Access to Optically Active Substituted Mandelic Acid Esters - Chen, Diao; Liu, Jian-Guo; Zhang, Xu; Xu, Ming-Hua (Synlett, 2019)
A rhodium-catalyzed enantioselective addition of glyoxylates to arylboronic acids promoted by a simple chiral sulfinamide-based olefin ligand under mild reaction conditions is described. The reaction provides access to a variety of optically active substituted mandelic acid esters in good yields with up to 83% ee. The catalytic system is also applicable to pyruvate addition. The synthetic utility of this method is highlighted by a formal synthesis of the antiplatelet drug clopidogrel.
Keywords: asymmetric catalysis; rhodium catalysis; ligands; mandelic acid esters; glyoxylate; arylboronic acids